2019
DOI: 10.1590/1518-8345.3019.3218
|View full text |Cite
|
Sign up to set email alerts
|

Temporal pattern of tuberculosis cure, mortality, and treatment abandonment in Brazilian capitals

Abstract: Objective:to analyze the temporal pattern of tuberculosis cure, mortality, treatment abandonment in Brazilian capitals.Method:this is an ecological study whose data source was the Information System of Notifiable Diseases for Tuberculosis (Sistema de Informação de Agravos de Notificação para Tuberculose). For analysis of temporal evolution, regressions by join points were performed considering the annual percentage variation and the significance of the trend change with 95% confidence interval.Results:542,656 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
24

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 35 publications
0
30
0
24
Order By: Relevance
“…The model was adjusted assuming that the number of inflection points could vary from zero to two, which means a straight line or a line with three segments. A significance level of 5% was established in the time trend analysis (Sousa et al ., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The model was adjusted assuming that the number of inflection points could vary from zero to two, which means a straight line or a line with three segments. A significance level of 5% was established in the time trend analysis (Sousa et al ., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, for the analysis of APC, the results with p<0.05 or 95% CI only positive (increasing trend) or only negative (decreasing trend) were considered significant. 13 The formation of purely spatial clusters of AIDS deaths was analyzed using the spatial statistical technique of Scan scanning, using the Software SatScan, v.9.6 ® . This method consists of a circular geographic window that moves through the area of interest and, in this scanning, the circle includes different sets of neighboring areas, which are considered candidates to represent a possible cluster of the event.…”
Section: Objective Methodsmentioning
confidence: 99%
“…It was tested whether one or more points should be added to the linear model by Monte Carlo permutation, i.e., it was evaluated whether a line with multiple segments describes the model better than just a line. 13…”
mentioning
confidence: 99%
“…The study aimed to describe the temporal trend of tuberculosis cases according to gender and age group and to make predictions considering the current context in an endemic municipality of northeast Brazil. The study also showed a curious fact, that is, although tuberculosis most commonly affects men of the economically active and older adult age groups, there was a high incidence of the disease in women in the 15 to 59 years age group, an unusual phenomenon, compared with other studies carried out in Brazil and internationally [15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 64%